Legal measures for the prevention of oil pollution by ships and civil liability for oil pollution damage in South African marine and coastal waters - Chetty, Sarika (Institute of Marine and Environmental Law, 2015)
This paper will look at whether the legislation passed in South Africa aimed at preventing and prohibiting oil pollution, as well as current civil liability regimes for oil pollution accidents are adequate or if they fail to meet the standard required by international law. For instance, compensation for the damage and harm caused to the environment is vital in order to restore the sea and prevent further accidents. In terms of civil liability, South Africa ratified the Convention on Civil Liability, but failed to enact domestic legislation in terms of the Convention to regularly update current legislation so that the standards are high and enforceable in national law. The result was that South Africa was left financially unprepared to deal with future oil spills and prevention thereof.